Investimento em educação infantil e desenvolvimento econômico: uma análise para o estado de Sergipe - Santos, Maria Ocileide Dias (2023)
This dissertation aims to analyze investment in early childhood education and economic development in Sergipe, expanding the research to Brazil. To achieve this, it was necessary to discuss the importance of education for the process of economic development. Regarding the methodology, this work uses a qualitative and quantitative analysis of articles, books, websites in which data on enrollment in Early Childhood Education in the micro-regions of Sergipe were collected, over a period of eighteen years. The results collected show that during the period analyzed, there was a significant growth in enrollments in the state, however it was found that this number of enrollments has been reducing over the years. Finally, although the state has achieved a highly significant scenario in relation to enrollments, it is still not as far as the target is predicted.